Over 14% Efficiency Single‐Junction Organic Solar Cells Enabled by Reasonable Conformation Modulating in Naphtho[2, 3‐b:6, 7‐b′]difuran Based Polymer. Issue 13 (1st March 2021) - Zheng, Bing; Qi, Feng; Zhang, Yu; Zhang, Ming; Gao, Panfeng; Liu, Feng; Li, Tianchen; Wei, Donghui; Wan, Meixiu; Chen, Guangming; Huo, Lijun; Jiang, Lei
Abstract: As one kind of abundant product from renewable resources, furan and its fused‐ring derivatives, have provoked great interest in the context of developing efficient photovoltaic materials. However, the power conversion efficiency (PCE) of furan‐based photovoltaic materials has lagged behind its thiophene counterparts. In this work, in consideration of the ordered π–π stacking via extending conjugation to further improve the charge mobility, a novel furan fused‐ring derivative of naphtho[2, 3‐b:6, 7‐b′]difuran (NDF) based copolymer of NDF‐3T is designed and synthesized. Because of its favorable linear molecular conformation, the NDF‐3T possesses a high crystallinity, as well as ordered and dense π–π stacking. Subsequently, the NDF‐3T‐based device exhibits an efficient PCE of 14.21%, which is higher than that of the analogue naphthodithiophene (NDT) counterpart (10.86%). To the best of the authors' knowledge, the PCE is also the best record in furan‐based photovoltaic materials. More importantly, the development of line NDF shows great potential in construing highly efficient photovoltaic materials and can be referenced to other furan fused‐ring structures. Abstract : A novel naphtho[2, 3‐b:6, 7‐b′]difuran (NDF)‐based copolymer NDF‐3T is designed and applied in organic solar cells (OSCs). The champion device based on NDF‐3T/ ITIC‐4Cl shows a PCE of 14.21%, due to the favorable molecular conformational modulation. Importantly, 14.21% is the highest PCE reported for furan‐based single‐junction OSCs. Therefore, the NDF is shown to be a promising building block in organic electronic materials.